The Financial Variables of Water Filter Pot Mainly Raw Material Darmasaba Clay in Btikk-Indonesia - Normal, I. Nyoman (International Journal of Economics and Financial Issues, 2020)
The purpose of this study is: to calculate the cost of goods manufactured, determine the selling price, and recognize the value of the inventory of water filter pots made from Darmasaba clay. The results showed that the Pot water filter (DA 28.0 - DB 17.5 - T 14.0) at BTIKK-BPPT can be made from two different raw material compositions, namely: a) Darmasaba clay and husk in a ratio of 70%: 30%, hereinafter referred to as Water Filter Pot 70:30; and b) Darmasaba clay, husks and sawdust in the ratio of 60%: 20%: 20%, hereinafter referred to as Water Filter Pot 60:20:20; (2) The financial variables of Water Filter Pot 70:30 and Water Filter Pot 60:20:20 are focused on three main things, namely the cost of goods manufactured, the selling price, and the ending inventory. The cost of goods manufactured 70:30 Water Filter Pot is Rp 44,869.50 per kg, Rp 86.09 lower than 60:20:20 Water Filter Pot which is IDR 44,869.50 per kg. The selling price of the 70:30 Water Filter Pot is IDR 49,350.00 per kg, IDR 100.00 is cheaper than the 60:20:20 Water Filter Pot which is IDR 39,450.00 per kg. The estimated value of the ending inventory of 70:30 Water Filter Pot is IDR 25,306,398.12, IDR 48,554.64 lower than the 60:20:20 Water Filter Pot of IDR 25,354,951.16; and (3) The using of Darmasaba clay and husk raw materials in the ratio of 70%: 30% is more appropriate to be used as raw material for water filter pots (DA28.0 - DB 17.5 - T 14.0), because it has technical and financial advantages for get porous ceramic standardization. Keywords: financial variables, water filter pots, Darmasaba clay. JEL Classification: M41 DOI: https://doi.org/10.32479/ijefi.9470